2018
DOI: 10.1111/dom.13564
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the long‐term cost‐effectiveness of once‐weekly semaglutide versus dulaglutide for treatment of type 2 diabetes mellitus in the UK

Abstract: Aims Glucagon‐like peptide‐1 (GLP‐1) receptor agonists are appealing as glucose‐lowering therapy for individuals with type 2 diabetes mellitus (T2DM) as they also reduce body weight and are associated with low rates of hypoglycaemia. This analysis assessed the long‐term cost‐effectiveness of semaglutide 0.5 and 1 mg vs dulaglutide 1.5 mg (two once‐weekly GLP‐1 receptor agonists) from a UK healthcare payer perspective, based on the head‐to‐head SUSTAIN 7 trial, to inform healthcare decision making.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 42 publications
7
47
0
Order By: Relevance
“…Short-term cost-effectiveness analyses are intended to complement, rather than replace, long-term cost-effectiveness modelling, and can provide supportive evidence for the results of analyses that extrapolate over a longer time span. Our findings are similar to those of a previous long-term cost-effectiveness analysis of once-weekly semaglutide 1 mg versus dulaglutide 1.5 mg from a UK perspective, which found that once-weekly semaglutide 1 mg was associated with cost savings as well as improved outcomes [26].…”
Section: Strengthssupporting
confidence: 89%
See 1 more Smart Citation
“…Short-term cost-effectiveness analyses are intended to complement, rather than replace, long-term cost-effectiveness modelling, and can provide supportive evidence for the results of analyses that extrapolate over a longer time span. Our findings are similar to those of a previous long-term cost-effectiveness analysis of once-weekly semaglutide 1 mg versus dulaglutide 1.5 mg from a UK perspective, which found that once-weekly semaglutide 1 mg was associated with cost savings as well as improved outcomes [26].…”
Section: Strengthssupporting
confidence: 89%
“…The UK National Health Service (NHS) relies on value-based decisions to manage and allocate healthcare budgets and ensure that funded interventions represent good value for money [24,25]. In a recent long-term analysis, once-weekly semaglutide 1 mg was found to be cost-effective for the treatment of T2D in the UK, compared with dulaglutide 1.5 mg [26]. Short-term economic analyses, such as cost of control analyses, complement longer-term analyses and are useful to assess and easily compare the cost-effectiveness of multiple new treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In this analysis, there was a gain of 0.4 QALYs, in line with the 0.28 QALYs observed in our analysis in the Swedish setting. In the UK analysis 49 , in which the IQVIA CORE Diabetes Model was used, gains of 0.17 QALYs were observed with once-weekly semaglutide vs dulaglutide. All three analyses (in the Swedish, Canadian, and UK settings) show that once-weekly semaglutide remains dominant vs dulaglutide.…”
Section: Paɵents Inadequately Controlled On Meƞormin Paɵents Inadequamentioning
confidence: 99%
“…Glucagon-like peptide-1 (GLP-1) receptor agonists represent a highly efficacious class of interventions for the treatment of type 2 diabetes, with the injectable GLP-1 analogue onceweekly semaglutide shown to be both efficacious and cost-effective versus a variety of therapies [8][9][10][11]. However, until recently, GLP-1 receptor agonists have only been available in injectable formulations, which may have been a barrier to patient use compared with other modern treatment options such as sodium-glucose cotransporter-2 (SGLT2) inhibitors and dipeptidyl peptidase-4 (DPP-4) inhibitors, which are administered orally.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in the UK, injectable GLP-1 receptor agonists are only recommended as an intensification step for patients with inadequate glycaemic control following a triple therapy combination of metformin plus a DPP-4 inhibitor with a sulfonylurea, pioglitazone or an SGLT2 inhibitor, for whom insulin therapy would have significant occupational implications or weight loss would benefit other obesity-related comorbidities [6]. Given the efficacy benefits GLP-1 receptor agonists appear to offer, earlier intensification to such medications could overcome the documented and substantial therapeutic inertia in people with type 2 diabetes [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%